Akuntan dan Akuntansi Dalam Peran Cipta Realitas Sosial dengan Nilai-Nilai Etika - Nursanty, Ida Ayu Nursanty; Endang Kartini; Yusi Faizatul Octavia; Baiq Desthania Prathama (ARBITRASE: Journal of Economics and Accounting, 2023)
This study aims to examine accountants and accounting in the role of creating social reality with ethical values. This research uses a spiritualist-rationalist paradigm. The researcher highlights that when the social reality that is created is a social reality that is dry with ethical values, then this kind of social reality will have a big influence in shaping individual behavior to behave the same as the "color" of social reality that binds it, namely behavior that is dry with ethical values. (non-ethical behavior). This behavior can of course change if the social reality that surrounds it, namely social reality which is loaded with ethical values, is very conducive to directing this behavior towards ethical behavior. An accountant with a dynamic mind can make big changes in his profession. This study uses contemplation and deconstruction approaches. The contemplation approach is to carry out a rational thought involving "conscience" about the reality created by modernity. And carrying out deconstruction means inserting "the other" (which so far in modernism's view is in a marginal position) into an orbit that must or obeys, is taken into account is something that really needs to be done in the field of accounting. Contemplation and deconstruction can help accountants to make accounting changes more humane.